2011
DOI: 10.1007/s11064-011-0488-0
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hypothesis About Mechanisms Affecting Conduction Velocity of Central Myelinated Fibers

Abstract: The hypothesis that gap junctions are implicated in facilitating axonal conduction has not yet been experimentally demonstrated at the electrophysiological level. We found that block of gap junctions with oleammide slows down axonal conduction velocity in the hippocampal Schaffer collaterals, a central myelinated pathway. Moreover, we explored the possibility that support by the oligodendrocyte to the axon involves energy metabolism, a hypothesis that has been recently proposed by some of us. In agreement with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Different trials have in fact shown that the oxygen deprivation quickly affects the nerve fibers, either myelinated or unmyelinated, throughout the central nervous system (Adriano et al, 2011;Banasiak and Haddad, 1998). The results obtained regarding this parameter mostly agree with those obtained from previous publications (Singh et al, 2004a;Thakur et al, 2005;Tsarouchas et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Different trials have in fact shown that the oxygen deprivation quickly affects the nerve fibers, either myelinated or unmyelinated, throughout the central nervous system (Adriano et al, 2011;Banasiak and Haddad, 1998). The results obtained regarding this parameter mostly agree with those obtained from previous publications (Singh et al, 2004a;Thakur et al, 2005;Tsarouchas et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Data show that in untreated conditions, only 13% of consumed glucose is converted to lactate. This value increased to 60% when platelets were treated with atractyloside, a specific inhibitor of the mitochondrial adenine nucleotide translocator (ANT) and hence of the mitochondrial OXPHOS [Adriano et al., ].…”
Section: Resultsmentioning
confidence: 99%
“…The Chemiosmotic Theory (Mitchell, 1961) as it was formulated is a process that can only take place in organelle possessing double membrane systems forming closed compartments to entrap protons, such as mitochondrial cristae, bacteria and thylakoids. Here, for the sake of simplicity, we have considered the mitochondrial inner membrane, even though in recent years, it has been shown that the oxidative phosphorylation (OXPHOS), coupled to aerobic ATP synthesis, also occurs in extra-mitochondrial districts, as rod outer segment (OS ) disks (Calzia et al, 2014) (Calzia et al, 2013) (Bianchini et al, 2008) (Panfoli et al, 2009), myelin sheath (Ravera et al, 2009) (Ravera et al, 2011b) (Morelli et al, 2011) (Ravera et al, 2015), plasma membrane (Mangiullo et al, 2008) (Arakaki et al, 2003) (Arakaki et al, 2007 (Adriano et al, 2011) (Chang et al, 2012) (Lee et al, 2016) (Taurino & Gnoni, 2018) (Taurino et al, 2016) (Gao et al, 2017) extracellular vesicles shedding form cells, such as exosomes and microvesicles, which seem to carry an unsuspected metabolic signature (Panfoli et al, 2016). In particular, recent data indicate an active extramitochondrial OXPHOS in the endoplasmic reticulum of platelets which both have elevated ATP need but possess very little mitochondria (Ravera et al, 2018).…”
Section: Extramitochondrial Oxidative Phosphorylationmentioning
confidence: 99%
“…In fact, it was demonstrated that many biological membranes, devoid of closed compartments and of mitochondria, conduct OXPHOS with high efficiency (Calzia et al, 2010) (Roehlecke et al, 2013) (Mangiullo et al, 2008) (Panfoli et al, 2012) (Ravera et al, 2011b) (Ravera et al, 2013) (Ravera et al, 2018) , challenging the idea that it is exclusive of mitochondria, thylakoid and bacteria. Of particular interest are the reports of the ability of plasma membranes to synthesize ATP outside the cell, as they harbour the five complexes of respiration (Mangiullo et al, 2008) (Arakaki et al, 2003) (Arakaki et al, 2007) (Adriano et al, 2011) (Chang et al, 2012) (Lee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%